Chemical Characterization of Sub-micron Aerosols during New Particle Formation in an Urban Atmosphere - Vijay P. Kanawade; Sachchida N. Tripathi; Abhishek Chakraborty; Huan Yu (Aerosol and Air Quality Research)
Abstract While high concentrations of pre-existing particles tend to inhibit new particle formation (NPF) in the atmosphere, severely polluted megacities around the world are becoming hot spots for the latter. We measured the particle number-size distributions with a Scanning Mobility Particle Sizer (SMPS) in the urban environment of Kanpur, India, and discovered that particle bursts occurred on 82% of the observation days, indicating that new particles frequently formed from gaseous precursors despite the relatively high concentrations of pre-existing particles. During such events, Aitken-mode particles contributed more than 50% of the total particle mass. Additionally, we used a high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) to assess chemical changes in the sub-micron particles during NPF events. Because the HR-ToF-AMS can not detect particles smaller than 40 nm in diameter, however, it was not possible to investigate the chemistry driving the NPF. Our results indicated that oxygenated organic aerosols (OAs) constituted almost 77%—the largest fraction—of the sub-micron particles. The m/z 57 ion (C4H9+), a tracer of hydrocarbon-like OA (HOA), displayed significantly enhanced signal intensity during all of the NPF event days. Moreover, the increased proportion of organic ions, m/z 44 (CO2+), on these days suggested the presence of less volatile, highly oxidized OAs (LV-OOAs), revealing that the growth of new particles was mainly due to the condensation of low-volatility organic species. The substantially elevated signal intensity of amines (viz., CHN+, CH4N+, C2H4N+, C3H8N+, and C5H12N+) in the sub-micron aerosols during NPF further demonstrated that these nitrogen-containing organic compounds may have played a critical role in these events. Thus, our findings emphasize the relevance of amines to secondary aerosol formation in severely polluted urban environments.